Implementation of Food Security Decree on Fisheries Product in Indonesia: Case in Dangerous Food Aditives Application - Eko Waluyo; Bayu Kusuma; Hefti Salis Yufidasari (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Today, every food industry must putting food safety as a bottom line to keep their product on a high quality. Fisheries product must be keeping the role of food safety to keep consumers safe to consumed a fisheries product. Traceability is a system to keep the food safety of a product to be safe on consumer table. Indonesian government have been released some decree which regulating the food safety role as a consumers protection program. Regulation of Indonesian government should be examined on the effectiveness perspectives. This research is aiming on the effectiveness perspectives of Indonesian government decree implementation of food safety. Research method was using descriptive analysis. Research was found that implementation of regulation Indonesian government about food safety was lack of effectiveness to keep food safety on the fisheries product, especially from the food additives perspective. Law enforcement is an urgent issue on the food safety regulation.